Plant Growth under Natural Light Conditions Provides Highly Flexible Short-Term Acclimation Properties toward High Light Stress - Schumann, Tobias; Paul, Suman; Melzer, Michael; Dörmann, Peter; Jahns, Peter (Frontiers in Plant Science, 2017)
Efficient acclimation to different growth light intensities is essential for plant fitness. So far, most studies on light acclimation have been conducted with plants grown under different constant light regimes, but more recent work indicated that acclimation to fluctuating light or field conditions may result in different physiological properties of plants. Thale cress (Arabidopsis thaliana) was grown under three different constant light intensities (LL: 25 µmol photons m-2s-1; NL: 100 µmol photons m-2s-1; HL: 500 µmol photons m-2s-1) and under natural fluctuating light (NatL) conditions. We performed a thorough characterization of the morphological, physiological and biochemical properties focusing on photo-protective mechanisms. Our analyses corroborated the known properties of LL, NL and HL plants. NatL plants, however, were found to combine characteristics of both LL and HL grown plants, leading to efficient and unique light utilization capacities. Strikingly, the high energy dissipation capacity of NatL plants correlated with increased dynamics of thylakoid membrane reorganization upon short-term acclimation to excess light. We conclude that the thylakoid membrane organization and particularly the light-dependent and reversible unstacking of grana membranes likely represent key factors that provide the basis for the high acclimation capacity of NatL grown plants to rapidly changing light intensities.